Identification and Diversity of Insects Associated with Tim-Tim Coffee (Coffea arabica x Coffea canephora) in Rusip Antara, Central Aceh, Indonesia - Diah Fridayati; Marlina; Aidil Amar (Jurnal Penelitian Pendidikan IPA, 2026)
Coffee plantations support diverse insect communities that play key roles in pest regulation, pollination, and ecosystem stability. This study analyzed insect family composition, abundance, and community structure in the Tim-Tim (Typica) coffee plantation ecosystem in Rusip Antara Subdistrict, Central Aceh Regency, using different trapping methods. Sampling was conducted from May to September 2025 in one representative plantation block with three observation plots, each containing 25 coffee plants. Three types of traps were employed: light traps, yellow plate traps, and malaise traps. Insect community structure was analyzed using the Shannon–Wiener diversity index (H’), evenness index (E), and similarity index. A total of 2,659 individuals from 65 families were recorded, dominated by Hymenoptera, Diptera, Coleoptera, and Hemiptera. Light traps captured the highest number of individuals and exhibited the highest diversity (H’ = 2.34), reflecting the activity of nocturnal insects attracted to light. Yellow plate traps showed moderate diversity (H’ = 1.77) but the highest evenness (E = 0.80), indicating balanced diurnal insect communities. Malaise traps recorded lower diversity (H’ = 1.33) and evenness (E = 0.57), primarily capturing high-flying insects such as Diptera and Hymenoptera. Similarity analysis revealed moderate to low overlap among trap types, demonstrating that different traps capture complementary components of the community. These findings highlight the high insect diversity and ecological stability of the Tim-Tim coffee plantation and emphasize the importance of multiple trapping methods for understanding community structure and supporting natural biological control in sustainable coffee agroecosystems.